Factors Affecting Successful EFL Learning in an Indonesian Bilingual High School: a Study on the Students' Language Learning Strategies - Anis Etikasari (Universitas Ahmad Dahlan, 2022)
Language Learning Strategies (LLS) are the strategies that language learners use to enhance the effectiveness of their language learning process. Research has shown that the more language learning strategies used by EFL learners, the more effective learning occurs which can improve the learners’ English proficiency. Consequently, schools should be able to provide supports to encourage the use of LLS by their students. Therefore, this study investigates how PBHSY, a school that is able to significantly improve their students’ English proficiency, optimize their English curriculum, English teaching methodology, learning environment, and facilities to support their students’ LLS in learni